Untapped opportunities : an analysis of corporate-social enterprise partnerships in Germany - Knoth, Maxime Zoé Martine (2023)
The benefits that commercial firms reap from collaborations with social enterprises are examined in this master thesis. The study examines the direct advantages of such cooperation from a business perspective, a relatively unexplored topic in prior research. It is accomplished by employing a qualitative research approach. 11 respondents, who represented various businesses involved in collaborations with social enterprises, were questioned in semi structured interviews. In addition, secondary data sources were used to supplement the interview findings. The response to the research question, "What benefits exist for multinational corporations that engage in partnerships with social enterprises," may be summed up in five categories. These include employee retention, brand perception, expansion of expertise, opportunities for mutual growth and problem-solving, and the enlargement of market coverage by developing new markets and acquiring new clients. By addressing this research gap, the study adds to the existing wealth of literature by providing information on the practical advantages of working with social enterprises from a commercial perspective. Additionally, it broadens the theoretical framework by offering a more in-depth comprehension of how businesses view and collaborate with social enterprises. A conceptual process model is set through to help companies to collaborate, make long-term planning more effortless, and pinpoint development opportunities. The study serves as a valuable resource for companies considering or currently engaged in partnerships with social enterprises. The findings shed light on the advantages, challenges, and potential avenues for maximizing the benefits derived from such collaborations.